2002
DOI: 10.1111/j.1467-842x.2002.tb00350.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of self‐reported and measured height, weight and BMI in Australian adolescents

Abstract: Objective: To explore the relationship between self-repor ted weight and height to actual weight and height in older Australian adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
91
5
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 27 publications
26
91
5
5
Order By: Relevance
“…The capacity of estimated BMI based on reported measures to diagnose non-obese adolescents was satisfactory, since nine of ten adolescents that were not obese were correctly classified. This finding is consistent with other investigations 7,17,18 . Positive predictive value was lower than that observed in other reports with adolescents 7,21 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The capacity of estimated BMI based on reported measures to diagnose non-obese adolescents was satisfactory, since nine of ten adolescents that were not obese were correctly classified. This finding is consistent with other investigations 7,17,18 . Positive predictive value was lower than that observed in other reports with adolescents 7,21 .…”
Section: Discussionsupporting
confidence: 83%
“…Ambrosi-Randic & Bulian 6 also reinforce the role of lack of information on weight and height. Wang et al 17 and Tokmakidis et al 8 did not see any effect of gender on the accuracy of anthropometric measures.…”
Section: Discussionmentioning
confidence: 99%
“…BMI calculated from self-reported body weight and height in adolescents is reported to be less valid because of possible under-reporting of weight and overestimation of height (Crawley and Portides, 1995;Strauss, 1999;Wang et al, 2002;Brener et al, 2003;Shapiro and Anderson, 2003). Therefore, the number of overweight adolescents is likely to be underestimated in current study.…”
Section: Risk Factors For Overweight and Obesity In Adolescents S Cromentioning
confidence: 62%
“…Self-report of weight and height may affect accuracy of BMI values and lead to underestimation of the prevalence of OW. Indeed, it has been demonstrated that adolescents aged 415 years tend to underestimate their weight and overestimate their height (Wang et al, 2002b;Brener et al, 2003). However, according to Strauss (1999), calculations of BMI are less inaccurate in children since they tend to underestimate both weight and height.…”
Section: Discussionmentioning
confidence: 99%